Perancangan Board Game Edukasi Satwa Endemik Pulau Jawa Untuk Anak Usia 7 Hingga 11 Tahun - Syifa Usya Sya’ban; M. Lahandi Baskoro; Erik Armayuda (AKSA: Jurnal Desain Komunikasi Visual, 2021)
Indonesia is a country that has natural diversity, including unique animals. One of the islands of Indonesia that has such unique animals is Java Island. Java Island is an island that has rapid urban development and also has a unique diversity of animals. However, there are still many children who are not familiar with animals, especially endemic animals of Java Island, and the cause of these animals being threatened with extinction. In designing this board game using a method that has been adapted from the Game Design Process by Game Design Ed with data analysis conducting interviews with children from the age of 7 to 11 years to find out what board games have been played by children and the children's knowledge about Java endemic animals. The rules of the game in the design of the board game were adapted from the Pandemic board game by Matt Leacock and the Quartet card game by Gurubumi. With educational board games, it is hoped that children can discover and learn to understand the continuance of Java Endemic Animals that are threatened with extinction.